The present and future perspective of the forestry subsector of Peninsular Malaysia - Othman, Mohd. Shahwahid (1985)
The characteristics and the structure, conduct and performance of Peninsular Malaysia's forestry subsector are examined. Special attention is paid to the declining resourse base, the paucity of regeneration efforts and the high degree of fragmentation at all levels. The above factors manifest themselves in the primary processing and in the limited but increasing involvement in down-stream processing. Export performance and the increasing competition from other producers are noted. These and other problems are seen to be worsening and there is a dire need for government policies and strategies to alleviate them. The second aim of this study is to attempt to forecast the subsector's main characteristics in the year 2000. Efforts at conservation and replenishment and the reduction of forest areas for harvesting are noted. In 15 Years time it is expected that a small number (perhaps ten or fewer) of wholly or partly government owned Intergrated Timber Complexes (ITCs) will pay a much larger role in the timber subsector. Manufacturing will be geared towards for more downstream processing. In the field of exports there seems to be no early prospects of solution. The formation of a "Malaysia Incorporated" national timber trade associaton represented by both government and private organizations including participants from the Association of Bankers will go a long way towards finding remedies to problems experienced in the timber trade. Through this association a consolidated approach to market research and product development, cargo consolidation and shipping arrangement is possible. The association can play a role in improving trading facilities notably facilities at the port and sources of finance.